Developing an Interactive E-Module Based on Flipbook for Solid Geometry - Diva Nathania; Santri Chintia Purba; Jitu Halomoan Lumbantoruan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This research aims to develop an interactive E-Module based on flipbook on solid geometry material that is valid and feasible. The research method used is Research and Development (R&D). The development research model used is the level 1 development research model from Sugiyono. The research location is at SMPN 50 East Jakarta. Data collection techniques used are interviews, observations, and questionnaires. The results of the research are an interactive E-Module validated with an average material validation result from 2 validators with a percentage of 80% in the Feasible category, an average media validation result from 2 validators with a percentage of 91.8% in the Very Feasible category, and an average language validation result from 2 validators with a percentage of 88% in the Very Feasible category. Therefore, it can be concluded that the interactive E-Module based on flipbook on solid geometry material is valid and feasible for use in mathematics learning for seventh-grade junior high school students. Thus, it can be concluded that the interactive E-Module based on flipbook on solid geometry material is valid and feasible for use in mathematics learning for seventh-grade junior high school students.